Influence of Freezing Regimens on Cord Blood Serum Dielectric Properties - Gorobchenko, O. A.; Moshko, Yu. A.; Nikolov, O. T.; Nardid, O. A.; Lipina, O. V.; Gatash, S. V. (Problems of Cryobiology and Cryomedicine, 2004)
Using UHF dielectrometry method the temperature dependencies of the complex dielectric permittivity for water molecules of native and frozen samples of cord blood serum (CBS) were investigated within the interval 4-40°C. For all the investigated samples non-monotonous changes in ε′ at 7-9, 16-20, 26-28 and 36-38°C were found. It is established that under slow freezing down to -20°C the serum ε′ value is lower than in both native samples and those subjected to rapid freezing, this may be the cause of increase in the amount of bound water in the system due to the growth of serum molecules hydration. Rapid freezing results in the ε′ increase in CBS, caused by cryoaggregation processes and dehydration of macromolecules in it.